PARADOKS MEDIA SOSIAL: PENGUATAN DAN DISRUPSI KEHARMONISAN DALAM KELUARGA KATOLIK DI MERAUKE - Subu, Yan Yusuf; Gamu, Fransiskus Aknar (Kariwari: Jurnal Pendidikan Agama Katolik dan Pastoral, 2026)
This study is aimed to analyse the role of social media on the harmony of married couples, identify harmony inhibiting factors and to determine the pastoral strategies conducted by the Church. This study applied a descriptive qualitative method. Primary data were obtained through interviews, observation, and documentation involving 20 informants from 10 Catholic married couples at the Parish of Bunda Hati Kudus Wendu in Merauke. The result of the study shows that social media plays a dual role: on one hand, it strengthens communication and intimacy between couples; on the other hand, excessive use can trigger conflict, jealousy, and neglect of the partner. The main inhibiting factor is the time spent on social media, where it might reduce spousal attention. Responding to the intended issue the parish then organized seminars and special coaching to help families managing social media use wisely. This finding confirms the importance of digital literacy and pastoral guidance to maintain family cohesion in the digital era